2000
DOI: 10.1046/j.1365-3059.2000.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and wetness duration on conidial infection, latent period and asexual sporulation ofPyrenopeziza brassicaeon leaves of oilseed rape

Abstract: Experiments in controlled environments were carried out to determine the effects of temperature and leaf wetness duration on infection of oilseed rape leaves by conidia of the light leaf spot pathogen, Pyrenopeziza brassicae. Visible spore pustules developed on leaves of cv. Bristol inoculated with P. brassicae conidia at temperatures from 4 to 208C, but not at 248C; spore pustules developed when the leaf wetness duration after inoculation was longer than or equal to approximately 6 h at 12±208C, 10 h at 88C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 11 publications
0
61
0
Order By: Relevance
“…Analyses of data from these controlled‐environment experiments suggest that temperature is the main factor affecting the length of the incubation period ( t 1 or t 50 ) of both A‐group and B‐group L. maculans . Times to the appearance of the first leaf spot lesions and to the appearance of 50% of the lesions both decreased with increasing temperature from 5 to 20°C, suggesting that after ascospore infection, phoma leaf spot lesions will develop more rapidly in winter oilseed rape crops in autumn or spring than in winter, as with light leaf spot (Figueroa et al ., 1995; Gilles et al ., 2000). The results of the controlled environment experiments of Hammond et al .…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of data from these controlled‐environment experiments suggest that temperature is the main factor affecting the length of the incubation period ( t 1 or t 50 ) of both A‐group and B‐group L. maculans . Times to the appearance of the first leaf spot lesions and to the appearance of 50% of the lesions both decreased with increasing temperature from 5 to 20°C, suggesting that after ascospore infection, phoma leaf spot lesions will develop more rapidly in winter oilseed rape crops in autumn or spring than in winter, as with light leaf spot (Figueroa et al ., 1995; Gilles et al ., 2000). The results of the controlled environment experiments of Hammond et al .…”
Section: Discussionmentioning
confidence: 99%
“…Goodwin (2002) pointed out that the ecological features of Rhynchosporium and Ramulispora (=Helgardia) overlap; both pathogens cause eyespot on winter wheat and scald on barley, respectively, autumn through winter (Caldwell 1937;Fitt et al 1988), and their conidia are produced and germinate under low-temperature conditions (Caldwell 1937;Fitt et al 1988). Likewise, P. brassicae can infect its host and then produce new conidia at low temperatures (Gilles et al 2000). L. orchidicola has been isolated from plants growing in alpine and subalpine habitats in western Canada (Fernando and Currah 1995).…”
Section: Conidiogenesis Of M Gentianaementioning
confidence: 99%
“…Previous work on light leaf spot has produced information on the effects of temperature and wetness duration on the infection of oilseed rape leaves by P. brassicae conidia and the latent period in controlled environments, together with some validation of the results under field conditions (Figueroa et al ., 1995a, b; Gilles et al ., 2000a). According to these results, the minimum criterion for infection of leaves at 12°C and 18°C is a wetness duration of at least 16 h. Field experiments showed that the time from infection to sporulation (latent period) generally ranged between 150 and 250 degree‐days (accumulated mean daily temperature above zero).…”
Section: Introductionmentioning
confidence: 99%